Comparative study between ethanolic and chloroform extracts of mucuna pruriens seeds extract in male wistar rats for the screening of anti-ulcer activity - Srivastava, Kalyani; Amit , Kaushik; Srivastava, Amit Kishor; Gupta, Amresh (International Journal of Indigenous Herbs and Drugs, 2022)
Background: Well documented neuroprotective profile as well as antioxidant potential of mucuna pruriens seeds with lesser side effects, we are intended to compare study between ethanolic (MPEE) and chloroform extracts (MPCE) of mucuna pruriens seeds extract in albino Wistar rats for the screening of anti-ulcer activity. Materials and methods: The pylorus ligation induced ulcer was used to explore the activity of the ethanolic and chloroform extract. Male albino Wistar rats weighing 100-150g were selected and grouped them among normal control, standard (Omeprazole; 20mg/kg) and treatment groups (MPEE; 50 mg/kg and MPCE; 50 mg/kg) respectively. Results: In our study, the chloroform and ethanolic extract of the seeds of Mucuna pruriens showed antiulcer efficacy as evidenced by a considerable decrease in gastric volume, free and total acidities, ulcer index, and pH. Consequently it might be predicted that both the extracts prevent suppress gastric damage induced by aggressive factors. Preventive anti-oxidants like catalase (CAT) enzymes and reduced glutathione (GSH) constitute the first line of defense in order to combat reactive oxygen species. Conclusion: The ethanolic and chloroform extracts were significantly inhibited the growth of ulcers. Based on the findings, it was determined that the ethanolic extract had superior antiulcer activity over the chloroform extract. In comparison to ulcer control rats, the administration of herbal extract (50 mg/kg p.o.) raised CAT, SOD, and GSH levels, indicating its efficiency in reducing free radical-induced damage. The preliminary phytochemical investigation showed the presence of glycosides, flavonoids, carbohydrate, and tannins in the ethanolic extract, whereas glycosides, sterols, triterpines and tannins in the chloroform extract. The MPEE exhibited a better ulcer protective activity than the MPCE extract.